2013
DOI: 10.1016/j.cmet.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytes Regulate Primary Lymphoid Organs and Fat Metabolism

Abstract: Osteocytes act as mechanosensors to control local bone volume. However, their roles in the homeostasis of remote organs are largely unknown. We show that ablation of osteocytes in mice (osteocyte-less [OL] mice) leads to severe lymphopenia, due to lack of lymphoid-supporting stroma in both the bone marrow and thymus, and complete loss of white adipose tissues. These effects were reversed when osteocytes were replenished within the bone. In contrast, neither in vivo supply of T cell progenitors and humoral fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 33 publications
5
100
0
3
Order By: Relevance
“…These changes in hematopoietic cells under microgravity conditions are widely thought to be cell intrinsic. A recent study, however, showed that microgravity disrupts the osteocyte network accompanied with a reduction in B cells in the BM, and that the depletion of osteocytes leads to a decrease in B and T lymphocytes in the blood, due to the impaired development of stromal cells that support B cells in the BM and T cells in the thymus, respectively [14]. Moreover, recent studies have revealed that osteocytes embedded in the bone matrix have critical roles in regulating hematopoietic cells.…”
Section: Osteocyte and Hematopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in hematopoietic cells under microgravity conditions are widely thought to be cell intrinsic. A recent study, however, showed that microgravity disrupts the osteocyte network accompanied with a reduction in B cells in the BM, and that the depletion of osteocytes leads to a decrease in B and T lymphocytes in the blood, due to the impaired development of stromal cells that support B cells in the BM and T cells in the thymus, respectively [14]. Moreover, recent studies have revealed that osteocytes embedded in the bone matrix have critical roles in regulating hematopoietic cells.…”
Section: Osteocyte and Hematopoiesismentioning
confidence: 99%
“…A number of important roles for osteocytes in bone biology, such as mechanosensation and mineral metabolism, have been identified in previous studies [11]. A series of recent studies, including one by our group, has revealed the importance of osteocytes in the regulation of hematopoiesis [12][13][14]. In this review, we provide an overview of advances in our knowledge of regulatory mechanisms in the hematopoietic system by osteolineage cells in the endosteal area.…”
Section: Introductionmentioning
confidence: 99%
“…For example, osteocytes regulate osteoblasts to control not only bone remodeling but also the niche function of HSCs by receiving signals from the sympathetic nervous system (8). Furthermore, osteocytes regulate the microenvironment that supports lymph production by primary lymphoid organs, such as the BM and thymus, and fat metabolism throughout the body (9). In this article, we review the unique roles of bone-buried osteocytes as commanders of the HSC niche and regulators of multiple organs HSC niche inside bone First, the study of osteoblasts rather than osteocytes become a trigger for joint research of bone metabolism and hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…These results revealed that osteocytes maintained peripheral fat in cooperation with the central nervous system. 46 Thus, the bone tissue equipped with osteocytes orchestrates remote organs to maintain whole body homeostasis of immunity and fat metabolism ( Figure 3). Recently, osteocalcin produced by osteoblasts has been recognized as a critical homeostatic regulator of glucose metabolism by acting on pancreatic b cells and adipocytes.…”
Section: Role Of Osteocytes For Remote Organsmentioning
confidence: 99%
“…41 Using the mouse tail suspension system, we confirmed that microgravity on the hind limbs disrupts osteocyte cellular network in the bone tissue and reduces the number of lymphocytes in the suspended BM. 46 To elucidate whether osteocytes were critical for homeostasis of the immune system and even other organs, we used OL mice that manifested osteoporosis with defective mechanotransduction. 41 Ablation of osteocytes led to severe lymphopenia due to the lack of lymphoid-supporting stroma in both the BM for B-cell precursors and the thymus for T-cell precursors, and a marked loss of white adipose tissues.…”
Section: Role Of Osteocytes For Remote Organsmentioning
confidence: 99%